Cutaneous infection and bactaeremia caused by Erwinia billingiae: a case report. (September 2017) - Prod'homme, M.; Micol, L.A.; Weitsch, S.; Gassend, J.-L.; Martinet, O.; Bellini, C.
Abstract: Cellulitis and erysipelas are common skin infections usually caused by Staphylococcus aureus and streptococci. Gram-negative rods are rarely implicated. We report here a case of dermohypodermitis and bactaeremia caused by Erwinia billingiae, a Gram-negative bacteria usually pathogenic and epiphytic to pome fruit tree.